2018
DOI: 10.1080/2162402x.2018.1500106
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of disease aggressiveness influence outcome from immunotherapy treatment in renal clear cell carcinoma

Abstract: Renal clear cell carcinoma (RCC) is the most common type of kidney cancer and has a high propensity for metastasis. While treatment with immune checkpoint inhibitors, such as anti-PD-1, have shown modest improvements in survival for RCC, it is difficult to identify responders from non-responders. Attempts to elucidate the mechanisms associated with differential response to checkpoint inhibitors have been limited by small sample size making it difficult to detect meaningful associations. We utilized existing la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…Nowadays, immunotherapy has become an effective treatment method for advanced or metastatic cancers (Aoun, Rassy, Assi, Albisinni, & Katan, 2017;Hoos, 2016;Kamal, Cheng, Frost, & Amos, 2019). Mainly immunotherapy categories include monoclonal antibody immune checkpoint inhibitors (ICIs), therapeutic antibody, cancer vaccines, immune system modulators, cell therapy, and small synthetic molecule inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, immunotherapy has become an effective treatment method for advanced or metastatic cancers (Aoun, Rassy, Assi, Albisinni, & Katan, 2017;Hoos, 2016;Kamal, Cheng, Frost, & Amos, 2019). Mainly immunotherapy categories include monoclonal antibody immune checkpoint inhibitors (ICIs), therapeutic antibody, cancer vaccines, immune system modulators, cell therapy, and small synthetic molecule inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy has recently been identified as an effective methodology for advanced or aggressive cancers (Hoos, 2016 ; Aoun et al, 2017 ; Kamal et al, 2018 ). In addition, many studies have found that the tumor mutation burden (TMB) and neoepitopes in many cancer types are closely associated with immunotherapy (Kandoth et al, 2013 ; Brown et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy is rapidly attracting attention in cancerassociated treatment, because it has shown efficacy in some advanced and aggressive cancers. [4][5][6] At present, tumor-cell PD-L1 expression 7 and tumor-infiltrating lymphocytes 8 have been identified as biomarkers to assist in predicting the response of immunotherapy. However, not all patients show a good response to immunotherapy, with some having no response.…”
Section: Introductionmentioning
confidence: 99%